A aplicação da probatio levior em matéria de prova diabólica - Rodrigues, Sandro Bortoluzzi Madeira Lamêgo (2023)
The dissertation analyzes the formation of the judgment of fact through the production of evidence, focusing on the repercussion of insufficient evidence to the process. Its purpose is to analyze situations in which the parties are subjected to a case of probatio diabolica or devil’s proof. It departs from the premise that the judgment of the dispute based on the burden of proof rule (in its objective aspect) is not a satisfactory jurisdictional response, if the evidentiary insufficiency arises from the presence of diabolical proof imposed on both parties. It outlines as a problem to be answered whether there would be a judge's duty to correct the difficulties arising from the presence of diabolical proof in the process. It develops the hypothesis that there is an inherent duty to the jurisdictional function to correct the difficulties of evidentiary instruction when diabolical proof is present, reducing the evidentiary rigor for the formation of its conviction, from the application of the probatio levior. Objective: Its general objective is to analyze the main ways of coping with the diabolical proof already provided by the law or accepted by the legal literature. It has the specific objectives of characterizing the diabolical proof and its hypotheses of occurrence; determine the legal nature of probatio levior and its scope of application; and to investigate cases of application of probatio levior as a way of facing the diabolical proof in brazilian Law. Methodology: the research is developed through a qualitative approach, from the reading of the collected bibliographical and documentary material, constituted by the existing legal literature on the researched topic, including books, theses, dissertations and scientific articles. It proceeds to search and read foreign bibliographic material — in particular, Portuguese, Italian, German, Spanish, Argentinean, North American and French legal literature —, as it is the primary source of discussion regarding various points of the research, as well as in reason of the scarcity of Brazilian works that promoted an analysis of probatio levior. It also conducts case analyzes, aiming to verify exemplary cases of judicial decisions in which the probatio levior technique was applied, even without its express recognition and mention. The research is developed through the deductive method, as it proves to be more suitable for achieving the proposed objective. Results: It was found that the legal system must have a satisfactory response to the pathology created by the diabolical proof in the process, since the evidentiary activity is also developed in the interest of the State and the jurisdiction. It confirms the established hypothesis, recognizing the existence of a duty imposed on the court to reduce the standard for the decision. Based on the observed problem — difficulties arising from the existence of diabolical proof in the process —, the need to apply an existing legal technique as a way of confronting it was recognized, through the elaboration of a theoretical model regarding the application of probatio levior. Contributions: the work stands out scientifically for systematizing the few existing sources on probatio levior, elaborating a propositional and pragmatic thesis, redefining the importance of the matter. In the practical aspect, it solves a procedural problem arising from the existence of diabolical proof, recognizing the duty to apply the probatio levior as a corollary of the inalienability of the jurisdiction. From the social point of view, it allows for satisfactory protection of rights to be given to those under jurisdiction, avoiding the rendering of decisions based on mere judgment based on the burden of proof.